Boundary spanners catalyze cultural and prescribed fire in western Canada - Hoffman, Kira M.; Copes-Gerbitz, Kelsey; Dickson-Hoyle, Sarah; Bourbonnais, Mathieu; Axelson, Jodi; Cardinal Christianson, Amy; Daniels, Lori D.; Gray, Robert W.; Holub, Peter; Mauro, Nicholas; Minocher, Dinyar; Pascal, Dave (Facets (Ottawa), 2024)
Western Canada is increasingly experiencing impactful and complex wildfire seasons. In response, there are urgent calls to implement prescribed and cultural fire as a key solution to this complex challenge. Unfortunately, there has been limited investment in individuals and organizations that can navigate this complexity and work to implement collaborative solutions across physical, cognitive, and social boundaries. In the wildfire context, these boundaries manifest as jurisdictional silos, a lack of respect for certain forms of knowledge, and a disconnect between knowledge and practice. Here, we highlight the important role of “boundary spanners” in building trust, relationships, and capacity to enable collaboration, including through five case studies from western Canada. As individuals and organizations who actively work across and bridge boundaries between diverse actors and knowledge systems, we believe that boundary spanners can play a key role in supporting proactive wildfire management. Boundary spanning activities include: convening workshops, hosting joint training exercises, supporting knowledge exchange and communities of practice, and creating communication tools and resources. These activities can help overcome unevenly valued knowledge, lack of trust, and outdated policies. We need collaborative approaches to implement prescribed and cultural fire, including a strong foundation for the establishment of boundary spanning individuals and organizations.